Analisis Penggunaan Media Sosial Instagram Sebagai Media Komunikasi Pemasaran Digital Pada Akun @ryuga.seafood - Siti Alfatya Ningrum; Silviana Purwanti; Johantan Alfando WS; Dony Kristian (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
Advances in information and communication technology have brought about significant changes in various aspects of human life, including marketing and business communication. Social media has become an essential tool for dynamic and rapid promotion, communication, and interaction. One of the most widely used social media platforms in this context is Instagram. Instagram is a promising platform for introducing products, reaching target markets, and building long-term relationships with consumers. This study aims to analyze how the social media platform Instagram in digital marketing communication activities shapes communication strategies through each element of the Integrated Marketing Communication (IMC) theory as utilized by the @ryuga.seafood account via its Instagram content. Method The research employs a qualitative approach using a case study methodology, with data collection techniques including in-depth interviews with the owner and staff, observation, and documentation in the form of Instagram content. The research findings indicate that Ryuga Seafood digital marketing communication strategy demonstrates a strong alignment with the Integrated Marketing Communication (IMC) theory as the primary framework. In terms of marketing, Ryuga Seafood optimizes all IMC elements, namely Direct Marketing, Sales Promotion, Public Relations, Personal Selling, Advertising, Word-of-Mouth Marketing, Events and Experiences, and Interactive Marketing. In conclusion, this comprehensive integration ensures that every IMC element works synergistically to increase brand awareness, create positive customer experiences, and foster long-term loyalty.